Comparative bioenergy estimation of field crop rotations using perennial and annual grasses in the Rostov region - G. V. Ovsyannikova; G. V. Metlina; S. A. Vasilchenko (Зерновое хозяйство России, 2020)
Annual and perennial grasses are important not only as a source of green fodder, hay, silage, grass meal and haylage in feed production, but also as good forecrops, due to the ability to accumulate biological nitrogen in the soil (since it decreases the cost of mineral fertilizers), to disinfect the soil from micro zoo pests, to improve the physical condition of the soil (since it decreases soil density). Perennial grasses are also an important component of biologized crop rotations, since the amount of crop residues remaining in the soil after harvesting is several times greater than after winter crops. The field trials were conducted in 2009–2016 by the staff of the laboratory of row crop cultivation technology of the FSBSI “Agricultural Research Center “Donskoy”. The experimental plot is located in the southern soil-climatic zone of the Rostov region (with insufficient and unstable moisture). The soil of the experimental plot is ordinary heavy loamy chernozem on loesslike loams, with 3.2% humus, neutral pH, and a high content of movable phosphorus and exchange potassium according to Machigin. The current paper has presented a bioenergetic estimation of grain (4-crop rotation sequence with annual grasses included) and biologized (8-crop rotation sequence with 25% perennial grasses) crop rotations. It has been established that nutrients’ amount per 1 ha of crop rotation area of biologized crop rotation is higher than in grain crop rotation on 22% of dry matter, on 40% of raw protein and on 39% of metabolic energy. Energy consumption per 1 kg of raw protein is lower on 27%.